Religious Guidance Through Weekly Prayer Meetings At The Nur Qolbu Sampit Mosque - Syarifudin; Ahmad Syarif (Jurnal Hadratul Madaniyah, 2026)
This study examines the implementation of religious guidance through weekly recitations at the Nur Qolbu Sampit Mosque. The background of this study stems from the gap between the routine religious activities at the mosque and the limited depth of understanding and practice of Islamic teachings among the congregation. This study aims to analyze (1) the implementation of religious guidance through weekly recitations, and (2) the supporting and inhibiting factors in its implementation. Using a descriptive qualitative approach, data was obtained through observation, interviews with ustadz, mosque administrators, and congregations, as well as documentation studies. The results show that regular recitations are conducted through lectures based on classical texts, discussions, and interactive question and answer sessions. These  activities  have  been  proven  to increase  the  congregation's understanding of aqidah, fiqh, and akhlak, as well as have a positive impact on their worship, social behavior, and spiritual condition. The main supporting factors include adequate facilities, the competence of the ustadz, and the strong commitment of the mosque administrators. Conversely, inhibiting factors are related to fluctuating congregational attendance and differences in prior knowledge  levels. This study  emphasizes  the importance  of mosques  as centers for continuous religious education and provides recommendations for improving the effectiveness of mosque-based learning programs.